A call for weed research in industrial hemp (Cannabis sativa L). (7th May 2019) - Sandler, L N; Gibson, K A
Summary: Industrial hemp ( Cannabis sativa L.) is grown in more than 30 countries for fibre, seed and flowers, and acreage of cultivation is increasing globally. Hemp has long been promoted as a crop that competes well with weeds and requires little intervention to prevent yield losses. We conducted a literature review and found little peer‐reviewed research to support this claim. We identified only three articles that specifically addressed weed management under field conditions and none provided information on hemp yield losses from weeds. These findings highlight a clear need for research‐based information on interactions between weeds and hemp to address potential yield losses under various production conditions and provide a research‐based framework for weed management in industrial hemp.